Etika Komunikasi Dalam Berdakwah - Harahap, Barkah Hadamean (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2019)
Communication cannot be separated from moral ties that implicitly constitute the nature of communication agents to be treated politely. The extent to which the details of communication ethics in preaching in the era of information globalization, this paper will attempt to discuss exposure regarding the intended theme. The purpose of this study. To study Da'i's Ethics in Da'wah .. The method of approach used in this research is library research, with descriptive analysis method. The results of the preacher's research when communicating should hold on to a strong ethical foundation, both an ethical foundation relating to norms that apply in society and that have been firmly implied in religion as the main source of ethics.